Natural language processing in light of neurolinguistic programming;Challenges and Arabic language solutions. (Numerus academy review, 2026)
The The language presents researchers and developers of natural languageprocessing (NLP) applications for text and speech grounds that some languages iscontrasts with others n lingos phonetically, morphologically, syntactically, andsemantically, starting from a discussion the general features of the language, and then specific properties of the language, and the challenge these properties pose to ANLP.This article discusses different challenges of NLP in Arabic and presents somesolutions that would guide current and future practitioners in the field of Arabic natural language processing (ANLP)..